Federal Republic of Nigeria Approved budget : 2000 fiscal year - Federal Republic of Nigeria (Abuja : Budget Office of the Federal Ministry of Finance, 1999)
This book is the 2000 fiscal year approved budget of the federal government of Nigeria.
Volume II: 2000 fiscal year
.
osa; 04/07/18
Arch
Keywords: Budget; Nigeria